2007
DOI: 10.2527/jas.2006-404
|View full text |Cite
|
Sign up to set email alerts
|

Long-term feed intake regulation in sheep is mediated by opioid receptors1

Abstract: These experiments were conducted to determine if 1) syndyphalin-33 (SD33), a mu-opioid receptor ligand, affects feed intake; 2) SD33 effects on feed intake are mediated by actions on opioid receptors; and 3) its activity can counteract the reduction in feed intake associated with administration of bacterial endotoxin. In Exp. 1, 5 mixed-breed, castrate male sheep were housed indoors in individual pens. Animals had ad libitum access to water and concentrate feed. Saline (SAL; 0.9% NaCl) or SD33 (0.05 or 0.1 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…which produced an increase in feed intake that was detected at 24 h and continued to at least 48 h after injection. Moreover, its effects were blocked by naloxone, indicating the feed intake response was mediated by opiate receptors (Obese et al, 2007). In a recent study in pigs, Kojima et al (2009) found a small increase in feed intake in pigs treated with SD33 just after weaning.…”
Section: Satiety-meal Terminationmentioning
confidence: 94%
See 1 more Smart Citation
“…which produced an increase in feed intake that was detected at 24 h and continued to at least 48 h after injection. Moreover, its effects were blocked by naloxone, indicating the feed intake response was mediated by opiate receptors (Obese et al, 2007). In a recent study in pigs, Kojima et al (2009) found a small increase in feed intake in pigs treated with SD33 just after weaning.…”
Section: Satiety-meal Terminationmentioning
confidence: 94%
“…Enkephalin expression in the PVN and VMN, both areas involved in satiety, was reduced in thin as compared with fat ewes (Henry et al, 2000) but long-term undernutrition had no effect on prodynorphin mRNA in sheep (Iqbal et al, 2003). Injection of the opiate antagonist naloxone was found to inhibit feed intake in sheep, suggesting a stimulatory role for opiate receptors in regulating feed intake (Alavi et al, 1991;Obese et al, 2007), though naloxone was ineffective in alteration of feed intake in pigs (Baldwin and Parrot. 1985).…”
Section: Satiety-meal Terminationmentioning
confidence: 99%
“…Serum prolactin concentrations and area under the prolactin curve (Table 5) were not affected by treatment (P ≥ 0.20), and there was no treatment × time interaction (P = 0.41). Prolactin was employed as an indirect indicator of opioid peptide action because opioids have been widely implicated in feed intake regulation (Obese et al, 2007). Hart and Cowie (1978) reported that i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that opioids administration increases food intake in rats (Woods and Leibowitz, 1985) and sheep (Obese et al, 2007;Verbeek et al 2012), indicating a role of endogenous opioid peptides in feeding behavior. However, because of the bitter taste of morphine, we could not sure that bees would like to drink morphine when provided orally.…”
Section: Discussionmentioning
confidence: 99%